Positioning Excellence – Based Model of Business Performance Supported by Market Orientation and Organization Innovation Among The Small and Medium Scale in Binong Jati Knitting Enterprices, Bandung - EDDY SOERYANTO SOEGOTO (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
To keep sustaining in the high competition, the small and medium scale enterprises (SME) must be able to know the customer’s needs and wants. The SME having the market orientation will completely fulfill what the customers want considering that market orientation is the commitment of the SME business actors to give the additional values for the customers. It is demanded to support the organization innovation in order that it can create the positioning excellence of the enterprise expected to determine the business performance. The goal of the research is to test abusiness performance model by taking into account the positioning excellence supported by market orientation and organization innovation. The method used in this research is descriptive and explanatory method, using the craftsmen in Binong Jati Knitting Centre as the research sample consisting of 203 craftsmen. The statistical analysis used was serqual Equation Model with Lisrel 8,7 program. The result of the research shows that in the operation the businessactors of Binong Jati Knitting SME pay little concern toward the market orientation in conducting their business; the business actors in general have not owned the innovative enterprises shown by the product innovation and the innovation in management process; the business actors have been able to place their e-Business in the high positioning excellence. Meanwhile, the business performance of Binong Jati Knitting SME is not proper yet especially in the pointof sales, profits, and market share achieved; the positioning excellence is influenced significantly positive by the market orientation and organization innovation. In the effort to improve the business performance, SME is recommended to implement the model simultaneously.